Establishing Baseline Indices for the Quality of the Biodiversity of Restored Habitats Using a Standardized Sampling Process - Feest, Alan (Restoration ecology, 2006)
The need for standardized biodiversity assessment methods to enable biodiversity quality to be measured is outlined. A general approach to sampling is suggested. The results of the use of this sampling process are given for two case studies of different taxonomic groups. The data assessment is made easier by the use of a bespoke computer program. Examples of the program output are presented. The advantage of this standardized measurement of biodiversity compared to species lists and the use of indicator species are outlined in the case studies macrofungi and butterflies. It was shown that the biodiversity quality of sites can be compared by the use of a range of measured biodiversity indices in a way that allows sites to be compared through time or between sites/treatments. In one case (butterflies), data that have been collected systematically in a recording scheme have been analyzed retrospectively and yielded valuable information on changes in biodiversity quality. The uses of this method in establishing baselines in restoration ecology are discussed. The importance of restoration ecology in the conservation of biodiversity could be underlined by the use of the methods presented in this article.